An Analysis of Trade Specialization in Bangladesh, 1996-2011 - Sikdar, Md. Mehedi Hasan (American Journal of Trade and Policy, 2019)
Trade specialization has been studied extensively, and many researchers try to explain the patterns of the specialization and different factors that determine it. By using the Revealed Symmetric Comparative Advantage Index and the Galtonian Regression Technique, this study tries to determine the industries with trade specialization and analyze the transformation of the pattern of trade specialization in Bangladesh in the period 1996-2011 to show how the export and import specialization of industries changed and to what extent the pattern of trade specialization in Bangladesh has been transformed during the last sixteen years. Empirical analysis showed that the export of Bangladesh consists mainly of the garment industry, and Bangladesh import products largely belong to the category of commodities for further production and the support of the exporting sector. From the Galtonian regression analysis of export and import specialization, it has been found that the level of export diversification is very low, relatively stable which is confirmed by the low mobility effect. Bangladesh’s export specialization pattern is highly concentrated only in apparel products over the whole study period, and all other sectors contribute with a significantly smaller amount in total export share, but import is more diversified. For the development of the country, it is necessary to diversify its export basket.